PENGARUH LINGKUNGAN BISNIS TERHADAP KINERJA UMKM (KASUS PADA SENTRA PENGOLAHAN IKAN DI KAMPUNG PATIN, DESA KOTO MESJID, KAMPAR, RIAU) - Rijal, Muhammad; Zuliarni, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to understand the influence of the business environment on the performance of UMKM. The population of this research is the whole business unit of fish processing in Kampung Patin, Desa Koto Mesjid, Kab. Kampar, Riau. The research is descriptive of quantitative research using census technique inside the sample collection. Of the population with 9 of respondents, wholly as sample. From 9 questionnaires, to all the questionnaires have been returned and can be processed.The results of research suggests that the business environment central in fish processing in central fish processing enterprises in Kampung Patin, Desa Koto Mesjid, Kab. Kampar, Riau is good. However the performance of small and medium macro entrepreneurs in central fish processing enterprises in Kampung Patin, Desa Koto Mesjid, Kab. Kampar, Riau not well. On the basis of the results of the analysis of data there are powerful relationship between the business environment with the performance of small and medium businesses UMKM. The direction of a relationship is positive, means the higher the business environment and has escalated the performance of small and medium businesses UMKM.Keyword: Business Environment, The Performance Of UMKM